2021
DOI: 10.1016/j.rmed.2021.106438
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of functional exercise capacity in patients with COVID-19: It is improved by telerehabilitation

Abstract: Background The impact of the COVID-19 pandemic on functional exercise capacity seemed quickly clinically evident. The objective of this study was to assess the functional exercise capacity of patients with severe COVID-19 and to evaluate the effect of a telerehabilitation program in the specific context of the COVID-19 pandemic. Method Patients hospitalized for severe or critical COVID-19 were recruited. The functional exercise capacity (one-minute sit-to-stand test (ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(117 citation statements)
references
References 17 publications
9
105
0
3
Order By: Relevance
“…This study was observational without a control group, for this reason it was difficult to determine how much of the improvement is due to the intervention itself and how much to the natural evolution of the disease. However, our results are in line with a previous study that applied a telerehabilitation program in 14 hospitalized patients (mean age 60.8 ± 10.4; 40% with ICU admission) [ 31 ]. The intervention group improve the 1-min STST by 10 points, and the control group improved 5 points.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study was observational without a control group, for this reason it was difficult to determine how much of the improvement is due to the intervention itself and how much to the natural evolution of the disease. However, our results are in line with a previous study that applied a telerehabilitation program in 14 hospitalized patients (mean age 60.8 ± 10.4; 40% with ICU admission) [ 31 ]. The intervention group improve the 1-min STST by 10 points, and the control group improved 5 points.…”
Section: Discussionsupporting
confidence: 92%
“…Close to half of the patients showed a 1-min STST below the 2.5 percentile at the beginning of the program and only 15% at the end. Our results are in line with another telerehabilitation program in COVID-19 which shows that this test can be an alternative to evaluate the effectiveness of a rehabilitation program [ 31 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“… 45 Severe or critical COIVD-19 patients after discharged, endurance exercises and muscles training for 3-week helped their functional exercise capacity. 46 Although these clinical data suggested that exercise helped the process of recovery in COVID-19 patients after discharge, subsequent data regarding exercise rehabilitation after SARS-CoV-2 infection are still limited. Accordingly, it is essential to understand the mechanism behind exercise promoting patients' rehabilitation, so as to precipitate the application of exercise in patients' rehabilitation plan.…”
Section: Exercise Intervention Helpful To Improve the Quality Of Life Of Covid-19 Patientsmentioning
confidence: 99%
“…For those, adapted exercise activity might be counted as a defense strategy and a preventive measure. For instance, home-based exercise can help to regulate the immune system and delay immunological aging in both non-clinical populations and COVID-19 patients [ 20 , 21 ]. Likewise, regular physical activity was associated with less distress and better well-being during the COVID-19 pandemic [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%